2020
DOI: 10.1016/j.ygeno.2020.08.023
|View full text |Cite
|
Sign up to set email alerts
|

A new graph-theoretic approach to determine the similarity of genome sequences based on nucleotide triplets

Abstract: Methods of finding sequence similarity play a significant role in computational biology. Owing to the rapid increase of genome sequences in public databases, the evolutionary relationship of species becomes more challenging. But traditional alignment-based methods are found inappropriate due to their time-consuming nature. Therefore, it is necessary to find a faster method, which applies to species phylogeny. In this paper, a new graph-theory based alignment-free sequence comparison method is proposed. A compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…It can be grouped into five clusters; namely H1N1 (blue), H2N2 (pink), H5N1 (red), H7N9 (black), and H7N3 (green). Our result is compared with the results in (Das et al 2020a ), (Sims et al 2009 ), (Dong et al 2019 ). The phylogenetic tree constructed by the Graph-theoretic method (Das et al 2020a ) shows one misclassification where A/Turkey/VA/505472–18/2007 (H5N1) (red) is placed in the cluster of H1N1 (blue).…”
Section: Results Analysissupporting
confidence: 58%
See 3 more Smart Citations
“…It can be grouped into five clusters; namely H1N1 (blue), H2N2 (pink), H5N1 (red), H7N9 (black), and H7N3 (green). Our result is compared with the results in (Das et al 2020a ), (Sims et al 2009 ), (Dong et al 2019 ). The phylogenetic tree constructed by the Graph-theoretic method (Das et al 2020a ) shows one misclassification where A/Turkey/VA/505472–18/2007 (H5N1) (red) is placed in the cluster of H1N1 (blue).…”
Section: Results Analysissupporting
confidence: 58%
“…The phylogenetic trees are constructed for these datasets using the UPGMA/NJ clustering method in MEGA11. The results from these datasets are compared with those of the formerly published methods that include the tri-nucleotide representation using J/J matrix method (Das et al 2018a ), the Graph-theoretic method (Das et al 2020a ), the Feature Frequency Profiles (FFP) method (Sims et al 2009 ), the Fuzzy Integral Similarity (FIS) method (Saw et al 2019 ), the Positional Correlation Natural Vector (PCNV) method (He et al 2020 ), the Multiple Encoding Vector (MEV) method (Li et al 2017 ), the Accumulated Natural Vector (ANV) method (Dong et al 2019 ). In most of the cases, it is observed that the appropriateness of the present results is better or equal to the results of the prior methods.…”
Section: Results Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, some synonymous codons are preferentially selected over others at higher frequencies, resulting in synonymous codon usage bias, and is found in almost all available genomes. This biased synonymous codon usage is not neutral but involved in nucleotide usage bias (72,73), mRNA stability (74, 75), translation accuracy, efficiency (76,77), and protein folding formation (78).…”
Section: Discussionmentioning
confidence: 99%